Oral sophocarpine protects rat heart against pressure overload-induced cardiac fibrosis. (August 2014) - Li, Jun; Li, Liudong; Chu, Hongxia; Sun, Xiaojian; Ge, Zhiming
Abstract Context: Sophocarpine, a tetracyclic quinolizidine alkaloid, is one of the most abundant active ingredients in Sophora alopecuroides Linn. (Kudouzi). Sophocarpine injection was found to have significant antiviral effects against coxsackievirus B3 and therapeutic effects for viral myocarditis in the clinic. Objective: This study assessed the effects of sophocapine on overload-induced cardiac fibrosis and investigated potential mechanisms. Materials and methods: Adult male Sprague–Dawley rats were subjected to a suprarenal abdominal aorta constriction (AC) or sham to induce sustained pressure overload. Six weeks later, rats were randomly assigned to receive sophocapine (10, 20, and 40 mg/kg, gavage) or vehicle treatment for an additional 6 weeks. Six weeks after treatment, cardiac dysfunction, cardiac coefficient, cardiac fibrosis, hydroxyproline concentration, and inflammation mediators were examined. Results: When compared with the model group, the left ventricular weight/body weight decreased by 25.4% and 39.0% in 20 and 40 mg/kg sophocarpine groups, respectively. The beneficial effects were associated with amelioration of left ventricular systolic pressure (LVSP) and left ventricular enddiastolic pressure (LVEDP). Moreover, pressure overload-induced cardiac fibrosis was attenuated in sophocarpine treated groups. Importantly, sophocarpine (20 and 40 mg/kg) decreased pro-inflammatory cytokine levels (IL-6, 14.6% and 18.5%; IL-1β, 23.1% and 32.6%), collagen content (27.7% and 50.1%), as well as matrix metalloproteinases-2, 9 (MMP-2, 9) expression (MMP-2, 11.8% and 18.5%; MMP-9, 16.2% and 21.1%). Sophocarpine (40 mg/kg) inhibited IκB-α phosphorylation (19.0%). Conclusion: These findings indicated that sophocarpine potentially had antifibrotic effects. The mechanism might be due to modulation of the balance between pro-inflammatory cytokine expression and collagen content level as well as MMPs expression via the NF-κB signaling pathway.